2008
DOI: 10.1111/j.1556-4029.2008.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

A Metric Method for Sex Determination Using the Proximal Femur and Fragmentary Hipbone*,†

Abstract: The pubic bone is considered one of the best sources of information for determining sex using skeletal remains, but can be easily damaged postmortem. This problem has led to the development of nonpelvic methods for cases when the pubic bone is too damaged for analysis. We approached this problem from a different perspective. In this article, we present an approach using new measurements and angles of the proximal femur to recreate the variation in the pubic bone. With a sample from the Terry Collection (n > 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 50 publications
2
41
2
3
Order By: Relevance
“…In addition to discriminant function analysis, the data was subjected to binary logistic regression analysis as previous studies [44][45][46][47][48], including a recent dental investigation [49], have suggested that it may be advantageous to use both statistical methods to estimate sex. As pointed out by these authors, the benefits of binary logistic regression are that this technique generally performs as well as or better than discriminant function analysis with fewer statistical assumptions when predicting dichotomous variables such as sex, and the resulting score used to classify an unknown individual also provides a probability value for the allocation.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In addition to discriminant function analysis, the data was subjected to binary logistic regression analysis as previous studies [44][45][46][47][48], including a recent dental investigation [49], have suggested that it may be advantageous to use both statistical methods to estimate sex. As pointed out by these authors, the benefits of binary logistic regression are that this technique generally performs as well as or better than discriminant function analysis with fewer statistical assumptions when predicting dichotomous variables such as sex, and the resulting score used to classify an unknown individual also provides a probability value for the allocation.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This is the reason why some authors have developed sex determination models using non-linear classification methods. For instance, Leguebe and Albert [3], Albanese [4], Torwalt and Hoppa [5], Francesquini et al [6] and Albanese et al [7] have analysed the predictive ability of logistic regression. Still others, such as Corsini et al [8] or Mahfouz et al [1] have analysed the ability of a neural network to build accurate models.…”
Section: Introductionmentioning
confidence: 99%
“…It is also dimorphic within the same population [5], and very useful in sexing skeletal remains. Several dimensions of the femur, including femoral head diameter, femoral length, and bicondylar breadth have been utilized for the allocation of sex in unknown skeletal individuals [1,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some geometric parameters of the proximal femur are associated with the risk of hip fractures [18][19][20], and sex differences in FNAL and FNW have long been noted in epidemiological studies [18][19][20][21][22]. Furthermore, the structural demands of the unrelated but sometimes conflictual functions of parturition and locomotion affected not only the pelvis but also the angle and length of the femoral neck [10].…”
Section: Introductionmentioning
confidence: 99%